Gastrointestinal Endoscopy in the Time of Covid-19 Pandemic: Current Guidelines and Experience From Indonesian Tertiary Endoscopy Centre - Hasan Maulahela; Jaffray DP Rambak; Hilda Nurmalihah; Kaka Renaldi; Achmad Fauzi; Murdani Abdullah; Marcellus Simadibrata; Ari F Syam; Roy Soetikno; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2020)
Coronavirus disease-19 (COVID-19) is a respiratory disease caused by novel SARS-CoV-2. The disease has become a global pandemic since March 2020. Transmission of the disease is rapid and contagious through droplets and contaminated environments. Meanwhile, gastrointestinal endoscopy is a procedure that has a high risk of transmitting COVID-19. Proper strategies are needed to prevent transmission of the virus in the endoscopic unit. Some literature has published the guidelines for prevent COVID-19 in endoscopic units such as guidelines by AGA, APSDE, ESGE and ESGENA. These guidelines state that strategies for prevent the COVID-19 transmission in endoscopy unit must be done from before the procedure, during the procedure until after the procedure. These strategies must be followed by all patients and health care providers who working in endoscopy units.